Impact of Prolonged Neoadjuvant Treatment–surgery Interval on Histopathologic and Operative Outcomes in Patients Undergoing Total Mesorectal Excision for Locally Advanced Rectal Cancer. Issue 6 (December 2020) - Akbaba, Ata C.; Zenger, Serkan; Aytac, Erman; Yozgatli, Tahir K.; Bengür, Fuat B.; Esen, Eren; Bilgin, Ismail A.; Sahin, Bilgehan; Atalar, Banu; Sezen, Duygu; Erdamar, Sibel; Kapran, Yersu; et al.
Abstract : Background: This study primarily aimed to assess the impact of prolonged neoadjuvant treatment–surgery interval (PNSI) on histopathologic and postoperative outcomes. Impacts of the mode of neoadjuvant treatment (NT) and surgery on the outcomes were also evaluated in the same patient population. Patients and Methods: Between February 2011 and December 2017, patients who underwent NT and total mesorectal excision for locally advanced rectal cancer were included. PNSI was defined as >4 and >8 weeks after short-course and long-course NT modalities, respectively. Results: A total of 44 (27%) patients received short-course NT (standard interval: n=28; PNSI: n=16) and 122 (73%) patients received long-course NT (standard interval: n=39; PNSI: n=83). Postoperative morbidity was similar between the standard interval and PNSI in patients undergoing short-course [n=3 (11%) vs. n=3 (19%), P =0.455] and long-course [n=6 (15%) vs. n=16 (19%), P =0.602] NT. PNSI was associated with increased complete pathologic response in patients receiving short-course NT [0 vs. n=5 (31%), P =0.002]. Compared with short-course NT, long-course NT was superior in terms of tumor response based on the Mandard [Mandard 1 to 2: n=6 (21%) vs. 6 (38%), P =0.012] and the College of American Pathologists (CAP) [CAP 0 to 1: n=13 (46%) vs. n=8 (50%), P =0.009] scores. Postoperative morbidity was similar after open, laparoscopic, and robotic total mesorectal excision [n=1 (14.2%) vs. n=21 (21%) vs. n=6 (12.5%), P =0.455] irrespective of the interval time to surgery and the type of NT. Conclusions: PNSI can be considered in patients undergoing short-course NT due to its potential oncological benefits. The mode of surgery performed at tertiary centers has no impact on postoperative morbidity after both NT modalities.